Measuring e-statement quality impact on customer satisfaction and loyalty - Bekhet H.A.; Al-Alak B.A. (Inderscience Publishers, 2023)
The purpose of this paper is to measure e-statement quality impact on customer satisfaction and loyalty, using a convenient sample from e-statement end-users in West Malaysia. Linear regression-stepwise technique was used to realise the objective of the study. Results show that customer satisfaction is significantly correlated with customer loyalty, implying that high customer satisfaction leads to a high level of customer loyalty. The paper clearly shows that the proper understanding of the true e-statement quality domains by bank management will enable the banking industry to design customer-oriented marketing strategies. The value of the study stems from the fact that it is the only paper of its kind that addresses this issue in Malaysia. Copyright 2011 Inderscience Enterprises Ltd.